Aspirasi Guru Terhadap Anak Berkebutuhan Khusus Dengan Minat Sekolah Rendah - Opi Andriani; Elfina Elfina; Juni Lestari; Misdhayanti Misdhayanti (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to find out about teachers' aspirations for ABK. The method used in this research is a literature review or literature review. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection for the literature study was carried out using the Google Scholar search tool. The screening results were appropriate and needed, there were 3 National Journal articles based on the articles found and analyzed. The results of this research found that teachers are so important for ABK that they hope to be able to help them develop their potential despite the shortcomings they experience. Teachers' aspirations for children with special needs with low school interest are the key to educational success, with the right support, appropriate training, and close collaboration between all parties involved better inclusive education can be realized, ensuring that all children have the opportunity to learn and develop appropriately. its potential.